2018
DOI: 10.19044/esj.2018.v14n3p67
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting for Groundwater Using the Continuous Vertical Electrical Sounding Method

Abstract: Abstract2-D CVES surveys using the Wenner configuration was carried out in 22 communities in the Tain District, Ghana. This was done with the objectives of assessing the subsurface geology, identify high groundwater potential zones for drilling high-yielding boreholes that could yield sustainable amount of groundwater. The collected resistivity data were converted from the apparent resistivity to 2-D model section using the least-square inversion algorithm with the help of Res2DInv software. The 2-D resistivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The resistivity method can be used to determine more accurately depths to bedrock, map graves, fracture zones which are capable of storing groundwater and preferential groundwater flow pathways (Aning et al, 2013a(Aning et al, , 2013bKnödel et al, 2007;Andrews et al, 2013;Nero et al, 2016). The ERI has been used to prospect for groundwater in all the major geologic formations in Ghana (Sikah et al, 2016;Issah et al, 2018).…”
Section: Resistivity Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistivity method can be used to determine more accurately depths to bedrock, map graves, fracture zones which are capable of storing groundwater and preferential groundwater flow pathways (Aning et al, 2013a(Aning et al, , 2013bKnödel et al, 2007;Andrews et al, 2013;Nero et al, 2016). The ERI has been used to prospect for groundwater in all the major geologic formations in Ghana (Sikah et al, 2016;Issah et al, 2018).…”
Section: Resistivity Methodsmentioning
confidence: 99%
“…According to Ewusi (2006) groundwater in the crystalline basement rocks in western section of the Savannah Region have yields between 135 l/min and 240 l/min at a depth ranging between 13 and 59 m. Kyere et al (2013) found out that in the Bawku West District, the aquifer zones were located between 10 and 40 m with yields within the range of 10 to 500 l/min in the Birimian and granitic rock formations. Issah et al (2018) revealed that in the Tain District, the aquifers are mainly in the weathered and fractured zones with depth in the range of 30 to 60 m and yields of 15…”
Section: Introductionmentioning
confidence: 99%
“…For instance, because of rich clay content shales have low resistivity (5 to 30 Ω m) while limestones, dolomites, and conglomerates show high resistivity (1000 to 100000 Ω me.g., Palacky, 1988) [53]. The geoelectrical method has found several uses in geophysics such as exploring the historic underground cities [12], characterizing the landslide geometry [13], identifying the sedimentary layers [10], determining the bedrock depth [54], studying the sedimentary layers for foundations [14], and searching for groundwater [15].…”
Section: Geoelectrical Methodsmentioning
confidence: 99%
“…In this respect, we consider the geoelectrical method alongside the Rayleigh surface waves in a joint manner to study the near surface Earth assembly. The geoelectrical method based on examining the electrical conductivity anomalies developing from variations from one rock unit to another one has found many uses in geophysics [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%